2015
DOI: 10.1007/s10519-015-9719-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences on Pubertal Development and Links to Behavior Problems

Abstract: Genetic influences on adolescent psychological development are likely to be mediated and moderated by pubertal hormones. Combining genetic analyses with advanced models of pubertal development, we extended work on the measurement and psychological significance of puberty. We examined how genetic and environmental influences on puberty vary by the way that development is described (logistic versus linear models versus traditional methods) and the different aspects of puberty (adrenarche vs. gonadarche), and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 62 publications
(120 reference statements)
2
17
0
Order By: Relevance
“…For instance, puberty in girls typically begins with a growth spurt in height, followed by breast budding, axillary and pubic hair growth, and ends with menarche, but the initiation of these events and the extent to which they overlap with each other varies across individuals (Marshall & Tanner, ). Although research in pubertal synchrony has been limited, there has been some consideration of the correspondence between adrenal and gonadal indicators of development (Corley, Beltz, Wadsworth, & Berenbaum, ; Susman et al., ). Most notably, Thompson, Hammen, and Brennan () reported that asynchronous pubertal development in girls was associated more strongly with depression in late adolescence.…”
Section: How To Capture Individual Differences In Pubertal Developmenmentioning
confidence: 99%
“…For instance, puberty in girls typically begins with a growth spurt in height, followed by breast budding, axillary and pubic hair growth, and ends with menarche, but the initiation of these events and the extent to which they overlap with each other varies across individuals (Marshall & Tanner, ). Although research in pubertal synchrony has been limited, there has been some consideration of the correspondence between adrenal and gonadal indicators of development (Corley, Beltz, Wadsworth, & Berenbaum, ; Susman et al., ). Most notably, Thompson, Hammen, and Brennan () reported that asynchronous pubertal development in girls was associated more strongly with depression in late adolescence.…”
Section: How To Capture Individual Differences In Pubertal Developmenmentioning
confidence: 99%
“…For example, there is some data to suggest that a faster tempo of pubertal maturation may be linked with poor psychological outcomes in high-risk girls (Mendle, Leve et al 2014). Moreover, recent twin-based genetic studies also highlight the importance of individual differences, as pubertal onset was found to be largely driven by genetic factors for both sexes, whereas non-shared environment had a larger impact on some models of progression or tempo (Corley, Beltz et al 2015). …”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Marceau and colleagues (2015) use an adoption design to examine if genetic risk for psychopathology, as indexed by biological mothers’ substance use, externalizing, and internalizing problems, was linked with children’s morning cortisol levels. Additionally, Corley, Beltz, Wadsworth, and Berenbaum (2015) use a longitudinal twin design to examine if genetic risk for adolescent substance use is linked with genetic influences on pubertal development.…”
mentioning
confidence: 99%